Efficiency of trickle irrigation and antitranspirants on nutrient availability and fruit production of Kinnow mandarin (Citrus reticulata Blanco) under rainfed condition - KUMAR, VIJAY; SINGH, PERMENDRA; KUMAR, MANOJ; KOTWAL, NEERAJ; KUMAR, SANJEEV (Journal of Soil and Water Conservation, 2025)
A field experiment was conducted during 2019 and 2020 at research farm of RRSS- SKUAST-Jammu to study the change of nutrient status and fruit production Kinnow mandarin through trickle irrigation and antitranspirants under rainfed conditions. The study was carried out in randomized block design in which fifteen treatments and replicated thrice. The two years pooled data was revealed that the maximum was obtained three days trickle irrigation intervals with foliar spray of kaolin (4%) of total chlorophyll (44.71), total water content (58.48 %), leaf water deficit (25.10 %), and leaf areas (45.24 cm) respectively. The range from organic carbon (4.43-4.54 g kg-1), available nutrients like nitrogen (209.27- 214.89 kg ha- 1), phosphorus (14.19-16.27 kg ha-1) and potassium (145.18- 157.31 kg ha-1) respectively were achieved. The leaf nutrient (N, P K, Ca and Mg) analysis exposed that three days trickle irrigation intervals with foliar spray of magnesium carbonate (4%) formed significantly (p<0.05) higher concentration of leaf primary and secondary nutrients than that three days trickle irrigation with foliar spray of kaolin (4%) in treated plants. The three days trickle irrigation intervals with foliar spray of kaolin (4%) observed that the highest in fruit yield (5775.45 kg ha-1) and TSS (10.93 0Brix) except juice content, reducing sugar total sugar. Overall, three days trickle irrigation intervals with foliar spray of kaolin (4%) antitranspirants might be support necessary water stress on ‘Kinnow’ mandarin plants of subtropical ecosystem humanizing their water productivity and fruit yield in water irregular condition.